Modelling Natural Gas Markets: Could We Learn from our Mistakes in the Past? - A Reality Check for MAGELAN - Andreas Seeliger (Institut für Energietechnik und Energiemanagement, Hochschule Niederrhein, 2023)
MAGALAN is a global gas market model developed in 2005 that provided forecasts until 2030 for gas production, international trade and other relevant parameters. As investors, policy makers and also researchers have a need of reliable model results, models should be faced with reality from time to time. This paper presents a reality check for some results from MAGELAN for the year 2020. Some forecasts show a very high accordance with actual figures (such as aggregated global gas production or total LNG trades), some other are far from recent developments in the real world (e.g. gas production of individual countries or realised capacities of specific pipeline projects). The paper finish with a brief discussion about reasons for the divergence between model and reality. Beside some improvements are likely with some updates to the model, major exogenous shocks will always be crucial for gas market modelling (respectively modelling in general). In that specific case, the “shale gas revolution” in the USA was such a major shock, that disturbed a wide range of gas market parameters.
Keywords: Q31; Q41; Q47; 330; Long term gas market modelling; Linear optimisation; Gas demand and supply; LNG